Analisis Persepsi Nelayan Perikanan Tangkap Terhadap Pembiayaan Bank Syariah - Muhammad Anhar; Ating Sukma; Sutisna Sutisna (Al Maal: Journal of Islamic Economics and Banking, 2021)
Kecamatan Palabuhanratu is a capture fishery base for fishing areas in the South of Sea Java and the Indonesian Exclusive Economic Zone (ZEEI) in the Indian Ocean. As most of fishermen in Indonesia, the majority of fishermen in Palabuhanratu still live in poverty. Poverty is caused by several factors, one of which is capital. The majority of fishermen want to add their capital by using conventional banks or moneylenders who charge them high interest, so they are getting poorer. This study aims to look at fishermen's perceptions of capital financing in Islamic banks. The research method used is the theory of planned behavior analysis (TPB) and structured equation modeling (SEM). The variables used in this study are subjective norms (SN), attitudes toward behavior (ATB), and perceived behavioural control (PBC). The results of data analysis show that SN, ATB, and PBC positively affect fishermen's perceptions of financing in Islamic banks. In addition, the SN and PBC variables positively affect the intention of fishermen to apply for financing in Islamic banks.